Refleksi Fonem Vokal Proto Austronesia Dalam Bahasa Melayu Dialek Langkat - Sari, Dewi Kumala (PASAI, 2013)
This research analyzes the reflexes of Proto Austronesia in Bahasa Melayu Dialek Langkat. The aim of this research is to compare the Proto Austronesiaâs vowel inflections of Melayu Dialek Langkat produced in Melayu Dialek Langkat. The analysis uses the concept of vowel inflections. The result of the analysis shows that the reflexes of vowel phonemes PAN in Bahasa Melayu Dialek Langkat occurs in linear and innovation forms. PAN vowel phonemes change into five vowel phonemes in Bahasa Aceh. The comparison of vowel phonemes changes of Proto Austronesia in Bahasa Melayu Dialek Langkat difference are: the difference changes of PAN phoneme *a in Melayu Dialek Langkat are found in vowel phoneme /o/, /u/, /i/, /|/ dan /E/. Phoneme *i in Melayu Dialek Langkat are found in vowel phoneme /a/, /e/, /o/ dan /E/. Phoneme *u in BA are found in vowel phoneme /i/, /o/, /|/, dan /E/. Phoneme *| in BA are found in vowel phoneme /a/ dan /o/. Based on the analysis of the data founds reflection of proto-Austronesian phonemes in Melayu Dialek Langkat.